Core competencies in cognitive-behavioral therapy : becoming a highly effective and competent cognitive-behavioral therapist - Newman, Cory Frank (New York ; London : Routledge, 2013)
"This volume is a concise, convenient, and clearly written book for those who wish to study, master, and teach the core competencies of cognitive-behavioral therapy. Relevant for novice therapists as well as experienced clinicians and supervisors, this text also goes between the lines of evidence-based practices to highlight those methods which maximize the motivational and inspirational power of this therapy. Dr. Newman focuses on ways in which therapists can make treatment memorable for clients, thus enhancing maintenance and self-efficacy. He also highlights the value system that is inherent in best practices of cognitive-behavioral therapies, such as clinicians commitment to earn the trust and collaboration of clients, to be humble students of the field for their entire careers, and to seek to combine the best of empirical thinking with warmth and creativity. Notably, this handbook also emphasizes the importance of therapists applying cognitive-behavioral principles to themselves in the form of self-reflective skills, good problem-solving, being role models of self-care, and being able to use techniques thoughtfully in the service of repairing strains in the therapeutic relationship. Newman's book provides many enlightening clinical examples, including those practices that otherwise eager therapists should not do (such as micro-managing the clients thoughts), as well as a plethora of transcript material that describes best supervisory practices. It does all this with a tone that is engaging, respectful of the reader, caring towards the clients, and optimistic about the positive impact cognitive-behavioral therapies when learned and used well can have on the lives of so many, clients and clinicians alike"--
"Core Competencies in Cognitive-Behavioral Therapy is the first book to address all of the core and clinical competencies involved in clinical practice. Like other authors in the Core Competencies series, Dr. Cory Newman presents the essential knowledge, skills, and attitudinal components of each competency, with an emphasis on application in clinical practice. He includes extended case material and session transcripts, and teaches readers necessary competencies such as making good use of session time, maximizing client learning and retention, making adjustments in protocol to maintain optimal collaboration with the client, and crafting therapy homework assignments. The overarching goal of the book, as with others in the series, is to teach readers to think and make decisions as a cognitive-behavioral therapist"--
Includes bibliographical references (p. 245-256) and index.
Keywords: Cognitive therapy; Psychotherapist and patient; PSYCHOLOGY / Cognitive Psychology; PSYCHOLOGY / Psychotherapy / Counseling; PSYCHOLOGY / Mental Health